Quality assurance in the era of individualized medicine - 4 0 16; 1959- Moumtzoglou, Anastasius S.; 5 (Hershey, PA : IGI Global, Medical Information Science Reference, 2020)
This book explores the science of individuality in the practice of health care quality and health services management--
Population health management, emerging technologies & the science of the individual / Anastasius Moumtzoglou, Abraham Pouliakis -- Model for determining process-wise CTQs for testing laboratory : case study / Pranil Sawalakne -- Security improvements for safer cross-border eHealth services in Europe / Dimitrios Katehakis, George Pangalos, Andriana Prentza -- The clinical laboratory and the comittment to quality : an update on best practices and regulatory requirements : new update on best clinical laboratory practices / Marilena Stamouli, Antonia Mourtzikou -- Digital transformation challenges for the implementation of quality electronic medical records / Dimitrios Katehakis, Angelina Kouroubali -- Case study Disys / Katerina Giazitzi -- Personalized nutrition recommendations in foodservices / Katerina Giazitzi, Vaios Karathanos, George Boskou -- Machine learning in healthcare, introduction and real world application considerations / Stavros Pitoglou -- Artificial intelligence and image analysis for the identification of endometrial malignancies : a comparative study / Abraham Pouliakis [and 14 others]
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: 2 -- 0; 6; methods -- Quality Assurance, Health Care;Precision Medicine -- 20; 20; 2